Synthesis of Directional Sources Using Wave Field Synthesis, Possibilities, and Limitations. (21st February 2007) - Corteel Corteel, E. E.
Abstract : The synthesis of directional sources using wave field synthesis is described. The proposed formulation relies on an ensemble of elementary directivity functions based on a subset of spherical harmonics. These can be combined to create and manipulate directivity characteristics of the synthesized virtual sources. The WFS formulation introduces artifacts in the synthesized sound field for both ideal and real loudspeakers. These artifacts can be partly compensated for using dedicated equalization techniques. A multichannel equalization technique is shown to provide accurate results thus enabling for the manipulation of directional sources with limited reconstruction artifacts. Applications of directional sources to the control of the direct sound field and the interaction with the listening room are discussed.